2021
DOI: 10.3389/fcimb.2021.671958
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Contribution of ABO, Lewis and Secretor Histo-Blood Group Carbohydrates in Infection by Toxoplasma gondii

Abstract: The glycosyltransferases encoded by genes from the human ABO, Lewis, and Secretor histo-blood group systems synthesize part of the carbohydrate antigens in hematopoietic and non-hematopoietic tissues. The combined action of these glycosyltransferases strongly influences cell, tissue, mucosa, and exocrine secretion carbohydrate phenotypes, including those serving as habitat for mutualistic and pathogenic microorganisms. A set of reports investigated associations between Toxoplasma gondii infection and the ABO h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Infection with T. gondii occurs through the gastrointestinal tract where the expression of the ABO blood groups glycoconjugates also occurs and thus ABO blood groups may influence the human susceptibility of this infection [ 21 ]. The combined action of glycosyltransferases encoded by genes from the human ABO, Lewis, and Secretor histo-blood group systems strongly influences cell, tissue, mucosa, and exocrine secretion carbohydrate phenotypes, including those serving as habitat for mutualistic and pathogenic microorganism [ 23 ]. Therefore, we determined the association between T. gondii infection and ABO and Rh blood groups in a large sample of people in Durango, Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with T. gondii occurs through the gastrointestinal tract where the expression of the ABO blood groups glycoconjugates also occurs and thus ABO blood groups may influence the human susceptibility of this infection [ 21 ]. The combined action of glycosyltransferases encoded by genes from the human ABO, Lewis, and Secretor histo-blood group systems strongly influences cell, tissue, mucosa, and exocrine secretion carbohydrate phenotypes, including those serving as habitat for mutualistic and pathogenic microorganism [ 23 ]. Therefore, we determined the association between T. gondii infection and ABO and Rh blood groups in a large sample of people in Durango, Mexico.…”
Section: Discussionmentioning
confidence: 99%
“…The sporulation time is between 2 and 21 days, and oocysts persist in the environment for a year or more, depending on the environmental conditions. 9 Previous study suggested that Toxoplasma antibodies are more prevalent in women who have cats or breeding cats at home than in women who do not breed and have cats. 6 To prevent and control cats from becoming infected, domestic cats must be fed sufficiently cooked meat and kept indoors to minimize scavenging or hunting.…”
Section: Discussionmentioning
confidence: 99%
“…8 Most cases of Toxoplasma gondii infection in humans are probably gained by sporulated oocyst ingestion in the soil or contaminated and polluted vegetables and fruits. 2 , 6 , 9 Nowadays, Toxoplasma gondii infection is recognized and considered to be a water-borne zoonotic disease, 10 this mode of transmission occurs where water treatment is ineffective. 10 , 11 Additionally, there is also an appreciation that sea mammals are becoming infected by waters from contaminated land areas and untreated urban sewage effluents.…”
Section: Introductionmentioning
confidence: 99%